K-State First: Student Satisfaction/Teacher & Course Evaluations: IDEA Student Ratings of Instruction - Eiselein, Gregory (Kansas State University. K-State First., 2015)
K-State First uses the IDEA form to evaluate instructors and courses. This document shows the percentage of first-year seminars and learning community classes that had "excellent course" and "excellent teacher" ratings at or above the national IDEA Database average.
Keywords: Assessments; Learning communities; First-year seminars; Fliers (printed matter)